Emerging role of Protein Kinase CK2 in Tumor immunity - Chen, Leichong; Zhang, Sijia; Li, Qianwen; Li, Junyu; Deng, Huilin; Zhang, Sheng; Meng, Rui (Frontiers in Oncology, 2022)
Protein kinase CK2, a conserved serine/threonine-protein kinase, is ubiquitous in cells that regulate various intracellular processes, especially in tumor cells. As one of the earliest discovered protein kinases in humans, CK2 plays a crucial role in phosphorylating or associating with hundreds of substrates to modulate several signaling pathways. Excellent reviews have reported that the overexpression of CK2 could be observed in many cancers and was closely associated with tumor occurrence and development. Its elevation is also an indicator of a poor prognosis. Recently, increasing attention has been paid to the relationship between CK2 and tumor immunity. However, there is no comprehensive description of how CK2 regulates the immune cells in the tumor microenvironment (TME), and the underlying mechanisms are still unclear. In this review, we systematically summarized the correlation between CK2 and tumor immunity, primarily the effects on various immune cells, both in innate and adaptive immunity in the TME. With the comprehensive development of immunotherapy as well as the mounting transformation research of CK2 inhibitors from the bench to the clinic, this review may provide vital information to find new treatment options for enhancing the efficacy of immunotherapy.